Uniqueness in inverse boundary value problems for fractional diffusion equations. (7th December 2015) - Li, Zhiyuan; Imanuvilov, Oleg Yu; Yamamoto, Masahiro
Abstract: We consider an inverse boundary value problem for diffusion equations with multiple fractional time derivatives. We prove the uniqueness in determining the number of fractional time-derivative terms, the orders of the derivatives and spatially varying coefficients.